2020
DOI: 10.3390/ijerph17186585
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Characteristics, Transport Pathways, and Potential Source Regions of PM2.5 and PM10 in Changchun City in 2018

Abstract: Air pollution has attracted increasing attention in recent years. Cluster analysis, scene analysis, and the potential source contribution function (PSCF), based on the backward trajectory model, were used to identify the transport pathways and potential source regions of PM2.5 and PM10 (particulate matter with an aerodynamic diameter of not more than 2.5 µm and 10 µm) in Changchun in 2018. In addition, the PSCF was slightly improved. The highest average monthly concentrations of PM2.5 and PM10 appeared in Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…To date, there have been some studies of PM 2.5 variation with firework displays, but most of the works have focused on individual cities [ 40 , 42 , 45 , 48 , 49 , 89 ]. However, considering that China has a large span of latitude and longitude, the climatic characteristics and geographical conditions are quite different, which makes the researches based on a single city have certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been some studies of PM 2.5 variation with firework displays, but most of the works have focused on individual cities [ 40 , 42 , 45 , 48 , 49 , 89 ]. However, considering that China has a large span of latitude and longitude, the climatic characteristics and geographical conditions are quite different, which makes the researches based on a single city have certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Before calculating the PSCF, the area which the trajectories pass through should first be grid-enabled. Different from the previous studies that the grid resolution was set to 1° × 1° or 0.5° × 0.5° (Meng et al, 2020;Yu et al, 2020), we set 0.1° × 0.1° resolution in order to show more details of the potential source area. The following equation expresses the PSCF:…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Countries implemented lockdown restrictions on their external borders and, in some cases, restricted internal traveling, social distance measures resulted in the significant reduction of transport flows, non-essential business (restaurants, fitness centers, shopping malls) were closed, industrial activities and constructions were minimized to a minimum level. All these activities are the main source of air pollution [16]. Mobility reports and scientific research has shown a decreasing trend of human movement in the affected countries.…”
Section: Introductionmentioning
confidence: 99%